Problem solving with C++ the object of programming - Savitch, Walter J. 1943- (Pearson Education Limited, 2018)
For courses in C++ introductory programming. Teach the fundamentals of C++ programming with an emphasis on problem solving Now in its 10th Edition, Problem Solving with C++ is written for the beginning programmer. The text cultivates strong problem-solving skills and programming techniques as it introduces students to the C++ programming language. Author Walt Savitch's approach to programming emphasizes active reading through the use of well-placed examples and self-tests, while flexible coverage means instructors can easily adapt the order of chapters and sections to their courses